Pro Kontra Zakat Mustaghallah - Irdlon Sahil (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2018)
Mustaghallah is something that is leased like gold and silver jewelry whose levels do not reach two hundred dirhams, rice fields, land, and so on. Mustaghallah is something that benefits continue to grow and produce but the goods do not disappear or run out. The group of fuqaha is' modern, mustaghallah are assets which are not classified as the type of al-amwal al-zakawiyah (assets which are obliged to zakat) which are not used for personal or trade purposes but can generate large income either by renting them out or sell their products. The majority of traditional ulama and some contemporary scholars argue that mustaghallah is not compulsory for zakat, their reason being that there are no shari'ah statements in the Shari'ah texts which explain their zakat obligations. While the majority of contemporary scholars and some traditional ulama argue that mustaghallah is obligatory for zakat, their reason is that the obligation of zakat is contained in mustaghallah even though there is no text explaining shari'ah, because the law will appear together with the existence of god.